Enhanced Killing and Antibiofilm Activity of Encapsulated Cinnamaldehyde against Candida albicans - Khan, Shahper N.; Khan, Shakir; Iqbal, Jawed; Khan, Rosina; Khan, Asad U. (Frontiers in Microbiology, 2017)
Candida sp. impelled opportunistic infection in immune-compromised patients ensuing from asymptomatic colonization to pathogenic forms. Moreover, slow spread of Candida species inducing refractory mucosal and invasive infections brings acute resistance to antifungal drugs. Hence, here we probed the effect of encapsulated preparation of Cinnamaldehyde (CNMA) in multilamellar liposomes (ML) against Candida albicans. The efficacy of ML-CNMA against Candida biofilm was assessed by scanning electron microscopy, transmission electron microscopy, as well as light microscopy and its percent inhibition, was determined by XTT and crystal violet assay. ML-CNMA showed more fungicidal activity than free CNMA as well as multilamellar liposomal amphotericin B (ML-Amp B), which was further confirmed by spot test assay and Log-logistic dose-response analysis. Antifungal activity was driven by reactive oxygen species (ROS) and cellular damage by sustained release of CNMA. Effect on hyphal formation during 48 hours in presence/absence of ML-CNMA was observed under a microscope and further substantiated by RT-PCR by amplifying HWP1, the gene responsible for hyphal wall protein formation. Apoptotic programmed cell death (PCD) was analyzed by FACS analysis which was further confirmed by cytochrome C (Cyt C) release assay. This study elucidates the mechanistic insight of the enhanced antifungal activity of ML preparation of CNMA against candida infections.